Sports and Bone Health: The Impact of Physical Activity on Bone Mineral Density - Bielecka, Larysa (Quality in Sport, 2025)
Introduction Bone health is a critical component in maintaining physical fitness and overall quality of life. Among the factors influencing bone tissue structure, an appropriate level of physical activity plays a pivotal role. Numerous studies in the literature report the beneficial effects of regular exercise on bone mineral density (BMD). Objective This study aims to review current scientific reports and summarize the state of knowledge regarding the impact of physical activity on bone mineral density. Materials and Methods A review of randomized controlled trials (RCTs) published between 2022 and 2024 was conducted to evaluate the effects of physical activity on bone mineral density. Four studies meeting predefined selection criteria were identified. Results The findings demonstrate that physical activity significantly impacts bone mineral density. Both aerobic and resistance training contribute to increased BMD. Resistance training, particularly when combined with other forms of physical activity or dietary interventions, offers notable benefits, especially in populations with excess body fat. Conclusions Regular physical exercise, particularly resistance training, plays a significant role in improving bone mineral density.